Characterization of purified human B(act) spliceosomal complexes reveals compositional and morphological changes during spliceosome activation and first step catalysis - Bessonov, Sergey (Cold Spring Harbor Laboratory Press, 2010)
To better understand the compositional and structural dynamics of the human spliceosome during its activation, we set out to isolate spliceosomal complexes formed after precatalytic B but prior to catalytically active C complexes. By shortening the polypyrimidine tract of the PM5 pre-mRNA, which lacks a 3′ splice site and 3′ exon, we stalled spliceosome assembly at the activation stage. We subsequently affinity purified human B(act) complexes under the same conditions previously used to isolate B and C complexes, and analyzed their protein composition by mass spectrometry. A comparison of the protein composition of these complexes allowed a fine dissection of compositional changes during the B to B(act) and B(act) to C transitions, and comparisons with the Saccharomyces cerevisiae B(act) complex revealed that the compositional dynamics of the spliceosome during activation are largely conserved between lower and higher eukaryotes. Human SF3b155 and CDC5L were shown to be phosphorylated specifically during the B to B(act) and B(act) to C transition, respectively, suggesting these modifications function at these stages of splicing. The two-dimensional structure of the human B(act) complex was determined by electron microscopy, and a comparison with the B complex revealed that the morphology of the human spliceosome changes significantly during its activation. The overall architecture of the human and S. cerevisiae B(act) complex is similar, suggesting that many of the higher order interactions among spliceosomal components, as well as their dynamics, are also largely conserved.